2019
DOI: 10.3389/fbioe.2019.00109
|View full text |Cite
|
Sign up to set email alerts
|

Physical Vein Models to Quantify the Flow Performance of Sclerosing Foams

Abstract: Foam sclerotherapy is clinically employed to treat varicose veins. It involves intravenous injection of foamed surfactant agents causing endothelial wall damage and vessel shrinkage, leading to subsequent neovascularization. Foam production methods used clinically include manual techniques, such as the Double Syringe System (DSS) and Tessari (TSS) methods. Pre-clinical in-vitro studies are conducted to characterize the performance of sclerosing agents; however, the experimental models us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, Bottaro et al showed that DSS foams demonstrate greater dwell times in the varicose PVM, while both Bottaro et al and Carugo et al demonstrate that DSS foams are more stable and exhibit longer dwell times in general. In conclusion, dwell time analysis reveals that foam performance from best to worst is PEM > DSS > Tessari (Bottaro, Paterson, Zhang, et al, 2019).…”
Section: Physical Characterization Of Sclerosing Foamsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, Bottaro et al showed that DSS foams demonstrate greater dwell times in the varicose PVM, while both Bottaro et al and Carugo et al demonstrate that DSS foams are more stable and exhibit longer dwell times in general. In conclusion, dwell time analysis reveals that foam performance from best to worst is PEM > DSS > Tessari (Bottaro, Paterson, Zhang, et al, 2019).…”
Section: Physical Characterization Of Sclerosing Foamsmentioning
confidence: 97%
“…Sclerotherapy involves the injection of a surfactant solution—using a needle or a catheter—that damages the inner vessel wall. This process involves the activation of calcium signaling and nitric oxide pathways in response to the sclerosant's injection, causing endothelial cell lysis, vascular fibrosis, and subsequent endovascular occlusion (Figure 3) (Bottaro, Paterson, Zhang, et al, 2019; Carugo et al, 2013; Eckmann, 2009). Upon injection, the efficacy of liquid sclerosants decreases due to dilution and rapid deactivation by blood components, making liquid sclerotherapy ineffective when conducted on larger veins such as saphenous veins (Cameron, Chen, Connor, Behnia, & Parsi, 2013; Carugo et al, 2015).…”
Section: Foam Sclerotherapymentioning
confidence: 99%
See 3 more Smart Citations